1997
DOI: 10.2741/a215
|View full text |Cite
|
Sign up to set email alerts
|

Cellular signaling in the bladder

Abstract: Embryologically, the urinary bladder is formed from endodermally derived epithelial cells and mesenchymal cells from the urogenital sinus and allantois. Experimentally, we have shown that bladder mesenchyme differentiates into bladder smooth muscle via an unknown signaling mechanism that originates from the urothelium. It is hypothesized that this signaling between the cellular types, occurs via growth factors. Evidence supporting this hypothesis is that a number of known growth factors, such as TGF beta 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 13 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…The expression of early G 1 phase cyclin-dependent kinases CDK4 and CDK2 and the lack of expression of late G 1 and S phase regulators such as CDK1, cyclin E, and cyclin A (Fig. 3A and B) confirm the quiescent nature of the urothelium and also explain at the molecular level the readiness of the urothelium to undergo renewal when provided with sufficient growth signals as would occur during wound healing (43).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The expression of early G 1 phase cyclin-dependent kinases CDK4 and CDK2 and the lack of expression of late G 1 and S phase regulators such as CDK1, cyclin E, and cyclin A (Fig. 3A and B) confirm the quiescent nature of the urothelium and also explain at the molecular level the readiness of the urothelium to undergo renewal when provided with sufficient growth signals as would occur during wound healing (43).…”
Section: Discussionmentioning
confidence: 89%
“…The lysates (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Ag of the total protein) were resolved by 7.5%, 10%, or 15% SDS-PAGE and transferred onto nitrocellulose membranes. After the membranes were reversibly stained with 0.1% Ponceau Red solution, they were blocked with 3% nonfat dry milk dissolved in TBST solution (10 mmol/L Tris-HCl, pH 7.5, 100 mmol/L NaCl, and 0.1% Tween 20) and incubated for 1 hour at room temperature with the primary antibodies in TBST with 1% nonfat dry milk [the antibodies were diluted 1:100, except for p53, p53 Ser 15 -P, MDM2 and CDK4 (1:200); cyclin D1, CDK1, cyclin A, and cyclin E (1:500); and Erk1,2 (1:5000)].…”
Section: Methodsmentioning
confidence: 99%
“…The results obtained with BMC matrix confirmed the importance of epithelium-mesenchymal interactions for the normal maturation of urothelium in vitro. Further works are required to identify the presence of growth factors, such as sonic hedgehog, keratinocyte growth factor and bone morphogenetic protein 4 [28], involved in the induction of urothelial differentiation onto the VM integrating BMC's matrix. But in a surprising way, the peptide growth factors potentially released by the BMC included within the matrix produced by the 1:1 mix mesenchymal population, failed to promote the vertical development of BUC and therefore the urothelium maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, changes of mRNA encoding TGF-␀ 1 in detrusor tissue after BOO have been reported in various experimental animal models [15,16] . Chul Kim et al [14] and Monga et al [9] further showed that urine TGF-␀ 1 was associated with BOO in human and rat models.…”
Section: Discussionmentioning
confidence: 99%